Singapore Defence Technology Summit – Why the Sky is not Falling : The Diffusion of Artificial Intelligence - Lockman, Zoe Stanley (2019)
While AI proliferation seems limitless and uncontrollable, what are the key ingredients necessary for organisations, particularly militaries, to leverage the technological enablers and limit unwanted diffusion?